ENVIRONMENTAL FACTORS AND ACADEMIC STAFF PERFORMANCE IN PUBLIC UNIVERSITIES IN RIVERS STATE - OKAI N. OKAI (International Journal on Integrated Education, 2020)
The study is on environmental factors and academic staff performance in public universities in Rivers State. Literatures relating to the study were reviewed for expert opinions. The purpose of the study is to examine how the environmental factors can facilitate the job performance of academic staff. Three research questions guided the study and three research hypotheses were postulated and statistically tested. ANOVA was used in testing the hypotheses of the study. The instrument for data collection was a questionnaire that was structured on Likert 4 point scale. The instrument was validated and the reliability was determined. The result of the study showed that physical facilities such as classrooms, office accommodation, and provision of health facilities influences the performance of academic staff in public universities, there was a significant relationship between physical facilities and academic staff performance; there was a significant relationship between the security of university environment and academic staff performance, there was a significant relationship between the provision of health facilities and academic staff performance in public universities. It was concluded that the university environments promote the effective performance of academic staff in the university. Recommendation among others include: that the university should provide more and adequate physical facilities, the university management should take the issue of security of staff more seriously, and staff should be educated on the use of facilities